THE DYNAMICS OF HOLOCENE – UPPER PLEISTOCENE PALEOCLIMATIC CHANGES IN CRIMEA ON THE MAGNETIC DATA OF THE EMINE-BAIR-KHOSAR CAVE SEDIMENTS - BONDAR, K.; RIDUSH, B. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Magnetic properties and palaeosecular variations of the Earth`s magnetic field are investigated along the section of horizontallylayered non-cemented loamy sediments from near-entrance part of the Emine-Bair-Khosar Cave. The dynamics of paleoclimatic changes on Chatyrdag plateau and surrounding area during Holocene – Upper Pleistocene is reconstracted from complex interpretation of magnetic, palaeomagnetic, palaeontological and radiocarbon data.